2018
DOI: 10.1590/s1980-220x2017005003284
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to whole blood donation, basic human needs and nursing diagnoses: a reflection

Abstract: A theoretical-Reflective study with the objective to reflect on human needs regarding the imbalance of whole blood donors considering adverse reactions to the donation, and the existing nursing diagnoses that best meet the imbalance needs. The following needs were pointed out according to the signs and symptoms of adverse reactions and based on the Theory of Basic Human Needs: skin and tissue integrity, emotional security, pain perception, body mechanics, oxygenation, physical integrity, physical comfort, elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
0
0
3
Order By: Relevance
“…The results showed that convalescent plasma donation was safe, which was similar to the results of this study 10 . In addition, many studies confirm that delayed adverse reactions, consisting mainly of vasovagal reactions and hematoma, usually occurred when a donor was just leaving the donation center or later 15,16 . There is a strong link between the occurrence of these adverse reactions and subsequent discontinuation of donations.…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that convalescent plasma donation was safe, which was similar to the results of this study 10 . In addition, many studies confirm that delayed adverse reactions, consisting mainly of vasovagal reactions and hematoma, usually occurred when a donor was just leaving the donation center or later 15,16 . There is a strong link between the occurrence of these adverse reactions and subsequent discontinuation of donations.…”
Section: Discussionsupporting
confidence: 88%
“…La situación de hospitalización genera en los pacientes y familias un estado de vulnerabilidad que se suma al de la enfermedad, y tiende a desequilibrar la capacidad de satisfacer sus necesidades básicas; en tal sentido, valorarlas y atenderlas es una prioridad (12). Para ello, es necesario contar con un enfoque holístico que permita contemplar al sujeto de cuidado en su plenitud como ser humano (13).…”
Section: Resultados Fase Iunclassified
“…ISSN 2675-6218 Ademais, toda transfusão é considerada um transplante, pois o sangue é um composto de diferentes células que podem gerar reações adversas no sistema imunológico, podendo ocasionar riscos sanitários, inclusive a morte (Esplendori, 2018).…”
Section: Recima21 -Revista Científica Multidisciplinarunclassified
“…Essas reações podem causar equimose, dor no braço, hematoma, reações alérgicas e febris. As reações mais incomuns à doação de sangue são fadiga, reação vasovagal, síncope, queda abrupta de pressão arterial ou hipoglicemia e lesão pulmonar aguda (Brasil, 2013;Esplendori, 2018).…”
Section: Recima21 -Revista Científica Multidisciplinarunclassified